Making Gems in Indian Alchemical Literature - Wujastyk, Dagmar (History of Science in South Asia, 2023)
This article examines the practice of producing factitious gems as described in Nityanātha’s Jewel Mine of Mercury (Rasaratnākara), a thirteenth to fifteenth-century alchemical work written in Sanskrit. It queries how this practice fits within the Indian alchemical discipline and explores its possible connections with other artisanal crafts.